Implementation of Al-‘Arabiyah Baina Yadaik in the Development of Maharah Istima’ and Maharah Kalam in Indonesian Islamic Boarding Schools - Afrau Qudsia Annainawa; Muhammad Nanang Qosim (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study examines the implementation of the Al-‘Arabiyah Baina Yadaik (ABY) Volume I textbook in developing maharah istima’ and maharah kalam among tenth-grade female students at Ma’had Riyadhush Shalihat (MARSHA), a female tahfidz Islamic boarding school in Boyolali, Central Java. The study employed a descriptive qualitative approach with a single-case study design. Data were collected through structured observation, semi-structured interviews, and documentation involving 12 female students and three Arabic language teachers over one academic year. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three interrelated aspects. First, the implementation was carried out through a teacher-internalized curriculum model supported by mufradat reinforcement in the dormitory three times daily. Second, the implementation accelerated learning achievement, as reflected in the students’ successful completion of Volume I and progression to Volume 2A within one academic year, accompanied by improvements in phonetic discrimination and listening comprehension skills. Third, a performance paradox was identified in which students were able to communicate spontaneously and functionally in Arabic within the dormitory environment but tended to remain passive during formal classroom instruction. This condition was influenced by language anxiety and peer pressure. The study underscores that the effectiveness of instructional material implementation requires the integration of learning systems, language-use environments, and students’ affective dimensions.